STRUCTURAL ANALYSIS OF THE MAIN SYSTEMIC PANCREATOGENIC COMPLICATIONS AND CAUSES OF MORTALITY IN ACUTE BILIARY PANCREATITIS - Ibadov, R.A.; Babadjanov, A.Kh.; Abdullajanov, B.R. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Structural analysis of the basic system pancreatogenic complications and causes of deaths in acute biliary pancreatitis. Material and methods: Under the supervision were 438 patients with biliary OP who were treated at the State University “republican specialized scientific and practical center of surgery behalf acad. B. Vahidov” and clinic of AndSMI in 2009-2018. Surgical interventions were performed 112 (25,6%) patients. More often - in 26 (5,9%) resorted to laparotomy, cholecystectomy (ChCE), drainage of the common bile duct, opening, sanitation and drainage of omental bursa. Results: Progression biliary pancreatitis characterized by the possibility of development of various multicomponent pancreatitis-associated systemic complications, against which the mortality was 11,4%. The main causal factor of poor prognosis were multiorgan failure such as the existence of acute respiratory distress syndrome (77,8%) and renal failure (48,1%), as well as septic manifestations (33,3%) and hemorrhagic complications (11,1%). Conclusions: The most common and significant complication of the system is the severe acute pancreatitis pancreatitis- associated acute respiratory distress syndrome, which is characterized by severe hypoxemia, requiring the immediate application of respiratory support, and progression of diffuse damage of the lung tissue.